A Young Aged Myocardial Infarction with Factor V Leiden Mutation and High Lipoprotein A Level - Yildiz, Abdulmelik; Bagirtan, Bayram; Karaca, Ilgin (Cukurova Univ, Fac Medicine, 2013)
Factor V Leiden (FVL) mutation has been shown tendency to thrombosis. Lipoprotein a (Lpa) is thought to be proatherogenic and prothrombotic. There are several publications that were reported that FVL mutation might be responsible for myocardial infarction especially in a young age group. 33 year old male patient was admitted to the emergency room with chest pain. Acute anterior myocardial infarction was diagnosed with electrocardiography. Coronary Angiography was performed. Coronary Angiography showed that there was a total occlusion in the proximal part of the left anterior descending artery (LAD). Other coronary arteries were normal. Complete patency was achieved with direct stent procedures in the completely occluded part of the left anterior descending coronary artery. FVL heterozygous mutation was found with polymerase chain reaction method. Elevated Lpa was found in the same period.
Keywords: Factor V Leiden mutation; Lipoprotein a; Acute myocardial infarction